Training and Counseling on Prevention of Typhoid Fever Transmission in Communities of Cempaka Public Health Centre in Banjarbaru - Norsiah, Wahdah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Typhoid fever is caused by Salmonella typhi and Salmonella paratyphi, which both of them are pathogenic in humans. Infection occurs due to swallowing food or drink contaminated with salmonella germs (Ministry of Health of the Republic of Indonesia, 2006). Prevention of typhoid fever can be accomplished by maintaining personal and environmental hygiene, including through vaccination, washing hands with water and soap, especially when preparing food or after going to the toilet. The aim of this community service is to increase knowledge about the causes and consequences of typhoid fever transmission and the importance of clean life behavior. The target for this activity is the community of Cempaka Village RT 23 Banjarbaru, totaling 50 people. Based on the results of IgG and IgM examinations, it was found that 3 people (6%) were positive and 47 people (94%) were negative. The level of public knowledge regarding typhoid fever after the education was carried out increased from the pretest results to good knowledge level of 6 people (12%) after posttest good knowledge level of 29 people (58%), pretest results low level of knowledge 27 people (54%) after posttest knowledge level low 60 people (12%). It is recommended for the community who got positive typhoid fever IgG and IgM examination results to complete treatment to prevent community to become a carrier. Monitoring of people's healthy and clean life behavior in terms of preventing transmission must continue to be carried out by the relevant agencies in order to prevent the impact of wider transmission on the surrounding environment.